Two new species of Neoperla (Plecoptera: Perlidae) from Southern China - Wang, Yingying; Wang, Guoquan; Li, Weihai; Tan, Fei; Tan, Mengchao (Zootaxa, 2026)
Two new species of the genus Neoperla, N. luocheng sp. nov. and N. pianma sp. nov. are described from Guangxi Zhuang Autonomous Region and Yunnan Province, China, respectively. The new species were assigned to the Neoperla (Formosita) sinensis-group and Neoperla (Formosita) lushana-complex. The new species were compared with related species in the subgenus.